Avaliação do ciclo de vida e do custo de uma edificação de concreto estrutural com diferentes traços: estudo do berço ao portão - Schmidt, Raquel Petry Brondani (2015)
Consumption and employability of concrete are widely recognized in the construction sector which is related to many environmental impacts. In this context, technical solutions that associate environmental sustainability and cost feasibility are needed. This case study aims to evaluate the sustainability of a structural concrete building executable in Santa Maria – RS integrating environmental and economic aspects. The concrete building was designed with two levels of compressive strength, 30 and 50 MPa, and two types of Portland cement, pozzolanic compound (CP II-Z) and pozzolanic (CP IV) were used, which experimentally originate four mixtures: II30, IV30, II50 and IV50. Considering the materials consumption, the Life Cycle Assessment was used to quantify the environmental impacts and the Life Cycle Cost to measure the associated initial cost, with a cradle-to-gate approach. The acquisition of raw materials, the production of concrete and the execution of the structure were considered for the building as a whole and as structural elements. The unitary analysis was the most expressive in order to present the results and it turns out that the increase of the concrete strength from 30 to 50 MPa favored the building sustainability. Differences between the results were more meaningful varying the fck than the cement type, with a slight preference for the CPIV one. Among the structural elements, the slabs offered the best performance, followed by stairs, beams and pillars. In addition, an overall analysis also suggests that the best alternative is the IV50 mixture.